IMPROVING STUDENTS'VOCABULARY BY VISUAL MEDIA - Parede, Mega Ryani; Mogea, Tini; Andreas, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this research is to determine whether or not employing cartoons and pictures may help children learn vocabulary more effectively. This study is a pre-experimental research project with a single group and a pre- and post-test design. This study's focus on the 25-student class of second graders at SMP Negeri 3 Bolangitang Timur for the academic year 2021–2022. There were 20 questions on the pretest and 20 questions on the posttest for the multiple choice test. The Hatch and Farhady mean formula was used to examine the data. The data analysis's findings demonstrate that the posttest's mean (7.0) was higher than the pretest's mean (4.16). In other words, after the intervention (visual media image and cartoon), the pupils' command of English vocabulary is improving. Thus, it is recommended that English teachers employ these methods in their instruction and learning to improve their students' vocabulary.